Oxidative Stress in People Living With HIV: Are Diverse Supplement Sources the Solution? - Esimebia Adjovi Amegashie; Ruth Oyawole Sikeola; Emmanuel Ayitey Tagoe; Elijah Paintsil; Kwasi Torpey; Osbourne Quaye (Health Science Reports)
ABSTRACT Background and Aim Antiretroviral therapy (ART) has reduced human immunodeficiency virus (HIV)/AIDS to a manageable chronic condition even though no cure exists. Despite ART control, latent HIV infection results in failed memory CD4 T‐cell responses, immune overactivation, inflammation, oxidative stress, genomic instability, deoxyribonucleic acid (DNA) damage, and premature CD4 T‐cell ageing. Overproduction of reactive oxygen species during oxidative stress can cause mitochondrial DNA damage, cancer, neurodegenerative and cardiovascular diseases, and premature aging in people living with HIV (PLWH). This review outlines current knowledge in oxidative stress among PLWH. Methods Google Scholar, Scopus, PubMed, and Science Direct were searched for literature conforming with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines from studies published from January 2013 to December 2023. A total of 75 studies from 22 countries were identified, with 52 studies carried out in human participants, 17 studies in cell lines, and 6 studies in animal models to assess oxidative stress levels. Results An increased oxidative stress with no changes in antioxidant levels was reported in HIV‐positive smokers, and those on substance abuse. Long‐term ART usage showed high levels of oxidative protein products and low levels of antioxidants when compared to short‐term ART usage. The use of supplements such as N‐acetylcysteine, selenium, and silibinin in animal models and cell lines showed increased cell viability, reduced reactive oxygen species, and increased antioxidant levels, which are promising therapeutic interventions that should be studied in PLWH to further help improve their disease outcomes. Conclusions Identifying extracts from natural and synthetic products with antioxidant effects will improve the general well‐being of PLWH.